A useful guide to research: Garbers, J G (ed) (1996) Effective research in the human sciences. Pretoria: J L van Schaik Publishers. ISBN 0-627-02165-4. 438 pages. - Collings, Steven J (PINS-Psychology in Society, 2026)
Effective research in the human sciences is designed to provide researchers, supervisors, and masters and doctoral students with practical guidelines that can be used to manage research programmes. The emphasis of the text is on the management of masters and doctoral training and research, with the general objective being lo augment or to supplement the conventional training in research methodology received by students in the human sciences.